2016
DOI: 10.1016/j.nut.2015.09.007
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro model to consider the effect of 2 mM glutamine and KNK437 on endotoxin-stimulated release of heat shock protein 70 and inflammatory mediators

Abstract: Please cite this article as: Marino LV, Pathan N, Meyer R, Wright VJ, Habibi P, An in vitro model to consider the effect of 2mM glutamine and KNK437 on endotoxin stimulated release of HSP70 and inflammatory mediators, Nutrition (2015), doi: 10.1016/j.nut.2015.09.007. This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
(72 reference statements)
0
3
0
Order By: Relevance
“…In a randomized, double-blind, interventional clinical trial in critically ill children with sepsis or surgery, glutamine supplementation maintained HSP70 levels for longer but did not increase glutamine levels and did not influence IL-10 or IL-6 levels and outcome [ 55 ]. Addition of 2 mM glutamine to the incubation media enhanced extracellular HSP70, TNF-α, and IL-10 release at 4 h and IL-8 at 24 h [ 56 , 57 ]. Increased release of extracellular HSPs was associated with repressed intracellular expression of HSP70 and HSP90α in sepsis [ 58 , 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a randomized, double-blind, interventional clinical trial in critically ill children with sepsis or surgery, glutamine supplementation maintained HSP70 levels for longer but did not increase glutamine levels and did not influence IL-10 or IL-6 levels and outcome [ 55 ]. Addition of 2 mM glutamine to the incubation media enhanced extracellular HSP70, TNF-α, and IL-10 release at 4 h and IL-8 at 24 h [ 56 , 57 ]. Increased release of extracellular HSPs was associated with repressed intracellular expression of HSP70 and HSP90α in sepsis [ 58 , 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increased release of extracellular HSPs was associated with repressed intracellular expression of HSP70 and HSP90α in sepsis [ 58 , 59 , 60 ]. As plasma from whole blood has been used in previous studies, discrimination of HSP70 released from granulocytes, lymphocytes, or peripheral mononuclear cells could not be established [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, administration of Gln enhanced the HSP70 expression through the crosstalk with the hexosamine pathway ( Figure 10). An in vitro study demonstrated that the promotion in HSP70 synthesis by Gln is accompanied by a favorable inflammatory response mediated by IL-8 and IL-10 [17].…”
Section: Heat Shock Proteins Genetic Regulationmentioning
confidence: 99%